From the Theory of Globalization to the Theory of Cultural Globalization: The Theoretical Search of Chinese Philosophers - Hong Zhao (Концепт: философия, религия, культура, 2024)
The article is devoted to the analysis of Chinese philosophers’ scientific positions on globalization and cultural globalization. With the ongoing debate on globalization, its current state and long-term consequences, it is of relevance to consider the non-Western perspective on the topic. The purpose of the study is to systematize the ideas of Chinese philosophers on globalization and cultural globalization. To achieve this goal, several tasks need to be solved: 1) to define the scope of ideas relevant to the research into the specificities of Chinese philosophical approaches to globalization; 2) to identify the specificities of Chinese philosophy as a science; 3) to consider key interpretations of globalization; 4) to clarify the different interpretations of cultural globalization and the globalization of culture and the grounds for distinguishing between them. The research materials are the works of Chinese philosophers, many of which are being introduced into scientific circulation outside China for the first time. The research methodology is based on the phenomenological approach and the systemic method, which allows the author to describe the development of the ways of conceptualizing the phenomenon of globalization in the works of Chinese philosophers as a holistic research process. The procedures of discourse analysis and the method of participant observation were also used. As a result, a systemic reconstruction of the process of conceptualization of globalization and cultural globalization in modern philosophy of China was obtained. The work notes that this process is still incomplete and identifies a group of authors working on it. It is established that the one specificity of the scientific nature of modern Chinese philosophy presupposes reliance on the ideas of Marxism and ideological guidelines formulated by the party leadership of the PRC, primarily Chairman Xi Jinping. Another is the focus on comparing significant ideas of foreign philosophers with Chinese traditional views and values. This allows adapting and incorporating the idea of globalization to the Chinese system of values and its plans for the strategic development as a leader in modern social processes. The analysis of interpretations of globalization in the works of Wang Zhengyi, Cai Tuo, Zhang Yihao and Chen Liuqing, Zheng Yiming and Zhang Chaoying allowed the author to trace the dialectical connection of economic and political ideas, which helps to substantiate the place of the Chinese economy in the context of globalization. Clarification of the features of the identification of cultural globalization by Wen Jun, Liu Huanming, Feng Jianjun and Li Deng allowed for the grounds for identifying China as a leader in building a harmonious world based on cultural diversity to be determined. Cultural globalization is interpreted as a supranational process of diversity in unity and unity in diversity, where China's role consists in harmonizing interaction. In turn, cultural globalization is understood as a consequence of the influence of globalization processes on the culture of China itself, which requires significant efforts to change the value content of borrowed ideas and concepts.